1997
DOI: 10.1073/pnas.94.5.1961
|View full text |Cite
|
Sign up to set email alerts
|

Transfection and overexpression of the calcium binding protein calbindin-D 28k results in a stimulatory effect on insulin synthesis in a rat β cell line (RIN 1046-38)

Abstract: Calbindin-D 28k , a calcium binding protein that is thought to act as a facilitator of calcium diffusion in intestine and kidney, is known to be regulated by vitamin D in these tissues. Calbindin-D 28k is also present in pancreatic ␤ cells, but its function in these cells is not known. To determine a role for calbindin-D 28k in the ␤ cell, rat calbindin-D 28k was overexpressed in the pancreatic ␤ cell line RIN 1046-38 by transfection of calbindin in expression vector, and changes in insulin mRNA were examined.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
27
0
2

Year Published

1999
1999
2016
2016

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 44 publications
0
27
0
2
Order By: Relevance
“…Under basal conditions changes in insulin mRNA were also not observed between vector transfected and calbindin-transfected cells (not shown). This differs from calbindin overexpressing high passage RIN 1046-38 cells, which showed a marked increase in insulin mRNA under basal condition when compared with vector transfected cells (19). High passage RIN cells differ from ␤TC cells because they are not glucose-responsive, and the insulin content of RIN cells (0.1% of normal islets) is much lower than the insulin content of ␤TC cells (20 -30% of that of normal islets; 20).…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…Under basal conditions changes in insulin mRNA were also not observed between vector transfected and calbindin-transfected cells (not shown). This differs from calbindin overexpressing high passage RIN 1046-38 cells, which showed a marked increase in insulin mRNA under basal condition when compared with vector transfected cells (19). High passage RIN cells differ from ␤TC cells because they are not glucose-responsive, and the insulin content of RIN cells (0.1% of normal islets) is much lower than the insulin content of ␤TC cells (20 -30% of that of normal islets; 20).…”
Section: Resultsmentioning
confidence: 92%
“…Although these studies and others (14 -17) established a link between the pancreatic ␤ cell and the vitamin D endocrine system and although the importance of calcium in insulin secretion is well known, there is still little information available concerning the exact mechanism whereby vitamin D may affect ␤ cell function. It has been suggested that the role of vitamin D in calcium metabolism of the ␤ cell may involve a genomic effect of 1,25-(OH) 2 D 3 , including the production of calbindin.Although isolated islets and perfused pancreas from vitamin D-deficient animals have previously been used to study the effects of 1,25-(OH) 2 D 3 on ␤ cell function (14 -17), recently we reported that the ␤ cell line R1N1046-38 contains both calbindin and receptors for 1,25-(OH) 2 D 3 and suggested that ␤ cell lines may provide a useful in vitro system for studying the effects of the vitamin D endocrine system on ␤ cell function (18,19). Although interesting data have been generated in numerous studies using RIN cells, the RIN cell line may not be the best model because these cells have little or no response to glucose and the insulin content of these cells is only approximately 0.1% of the insulin content found in the normal ␤ cell.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Reported functions for CB-D28k include a role in Ca 2þ resorption in the kidney (Boros et al 2009) and modulation of insulin production and secretion in pancreatic beta cells (Reddy et al 1997;Sooy et al 1999). Data on a putative neuroprotective role against excitotoxicity have not yet resulted in a consistent picture (for a review, see Schwaller et al 2002 andSchwaller 2009).…”
Section: Functional Aspects Of Cb-d28kmentioning
confidence: 99%
“…26,27 However, increase in calbindin consequently decreases intracellular free calcium, 28 with such intracellular free calcium decrease demonstrated to be important for subsequent inhibition of calcium-mediated apoptosis in multiple experimental studies. [29][30][31] Furthermore, in addition to studies indicating calbindin gene overexpression in mice colorectal adenomas, 32 a body of other evidence also indicates calbindin overexpression may stimulate cell growth and proliferation 33 as well as increase insulin levels, 34 which may also have cell proliferative effects for colorectal cancer. [35][36][37] However, modulation of vitamin D's effects by estrogen may also be important.…”
Section: Potential Mechanismsmentioning
confidence: 99%